Therapeutic Applications of Metal and Metal-Oxide Nanoparticles: Dermato-Cosmetic Perspectives - Pan, Sharadwata; Goudoulas, Thomas B.; Jeevanandam, Jaison; Tan, Kei Xian; Chowdhury, Shamik; Danquah, Michael K. (Frontiers in Bioengineering and Biotechnology, 2021)
Invention of novel nanomaterials guaranteeing enhanced biomedical performance in diagnostics and therapeutics, is a perpetual initiative. In this regard, the upsurge and widespread usage of nanoparticles is a ubiquitous phenomenon, focusing predominantly on the application of submicroscopic (< 100 nm) particles. While this is facilitated attributing to their wide range of benefits, a major challenge is to create and maintain a balance, by alleviating the associated toxicity levels. In this minireview, we collate and discuss particularly recent advancements in therapeutic applications of metal and metal oxide nanoparticles in skin and cosmetic applications. On the one hand, we outline the dermatological intrusions, including applications in wound healing. On the other hand, we keep track of the recent trends in the development of cosmeceuticals via nanoparticle engrossments. The dermato-cosmetic applications of metal and metal oxide nanoparticles encompass diverse aspects, including targeted, controlled drug release, and conferring ultraviolet and antimicrobial protections to the skin. Additionally, we deliberate on the critical aspects in comprehending the advantage of rheological assessments, while characterising the nanoparticulate systems. As an illustration, we single out psoriasis, to capture and comment on the nanodermatology-based curative standpoints. Finally, we lay a broad outlook and examine the imminent prospects.